Takhrij and Syarah Hadith of Agrotechnology Study of Planting Citrus Pest Free - Maghfira Putri Nurastuti; Wahyudin Darmalaksana; Ida Yusidah (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the study of planting citrus plants free from pests. This research method is qualitative through the takhrij and syarah hadith approaches. The results and discussion of this study is the use of appropriate activity methods, namely an expert system for diagnosing diseases and pests of citrus using the euclidean distance method or the shortest distance from each existing symptom against pests or citrus diseases. The conclusion of this study is that it is hoped that this method can help users to make it easier to find information about diagnosing pests and diseases so that they are free from pests and diseases and are suitable for sale as found in the Prophet's hadith.